Blockchain based privacy preserving multimedia intelligent video surveillance using secure Merkle tree - Lee, Donghyeok; Park, Namje (Multimedia tools and applications, 2021)
The recent intelligent surveillance systems provide various services that have not existed before, such as proactive predictive surveillance, through the AI-based video analysis technology. However, there are common security and privacy challenges caused by malicious attacker and untrusted 3rd party in the CCTV cloud system. To solve this problem, we exploit the blockchain technology to insure integrity and security of cloud-based intelligent surveillance system. In this paper, we propose a new method for cloud-based CCTV blockchain system. Our contribution is to propose a new Merkle-Tree method for the efficient transmission of video data. The suggested method in this paper is efficient because it reduces the bandwidth required for transmission. It also has the advantage of enabling deduplication to reduce storage costs. Also, the proposed method can synchronize CCTV video data safely without exposing the privacy of the object in the course of synchronization.